THE IMPORTANCE OF THE AUDIO LINGUAL METHOD IN TEACHING LISTENING - Novianty, Melisa (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2021)
Listening is theway to catch information accurately and the way to know what is the messages about in the process of communication. It means that the students here are be able to interprete what the speaker say.The way to listen is to pay attention to sound or action.In fact, in learning procesess, teaching listening faced some difficulties for the students. One of the reasons is as foreign language. Therefore, the writer tried to use one of methods in teaching listening. Such as: the audio lingual method.This method is very important to know, especially: how the principles of this method, what is the goals for the teachers and students, how about the roles for the teachers, how is the feelings of the students using this method, etc. In addition, to face those problems, this articleexplained some solutions to make the students more interesting in learning listening.